Efficacy of Eyesi surgical simulator training in improving high-tension capsules capsulorhexis performance - Bisol,Tiago (2016)
ABSTRACT Purpose: To evaluate if Eyesi cataract surgical simulator training using its standard course curriculum is effective in improving performance of cataract surgery trainees on creating capsulorhexis on high-tension capsules on the simulator. Methods: We retrospectively analyzed training reports of ophthalmic surgery trainees (2nd and 3rd year residents and cataract fellowship trainees) that have accomplished the standard Eyesi cataract surgery simulator training course version 2.1 between May 2012 and August 2013 at Instituto de Diagnostico e Terapia Ocular, Rio de Janeiro, Brazil. We compared the mean score (from 0 to 100) attributed by the simulator on performing the same task, a capsulorhexis on a high-tension capsule, on the surgical simulator "before training" (during beginning of the course) and "after training" (at later stages of the course). Results: Thirty-seven trainees' reports were analyzed. Mean and standard deviation "before training" high-tension capsulorhexis score was 41.73 ± 27.08 points and the mean "after training" score was 72.55 ± 16.40 points, a difference of +30.82 points (p value <0.001 on Paired t test), representing a 73% improvement on performance. Conclusions: Eyesi surgical simulator training on course version 2.1 curriculum was effective in improving performance of cataract surgery trainees on creating capsulorhexis on high-tension capsules.